Cooling Auction Fever: Evidence from the Housing Market - Gargano, Antonio; Giacoletti, Marco (Review of Financial Studies, 2026)
We study the effects of underquoting, the practice of setting listing prices below sellers’ reservation values, on housing auctions. Laws introduced in Australia to deter underquoting lead to higher listing prices, but also to declines in sales prices and sales probabilities. We develop a quantitative model to formalize predictions under different assumptions about bidders’ information and rationality. The effects of the laws are matched by a version of the model in which participating bidders overbid. While both behavioral biases arising during the auction and switching costs can explain overbidding, empirical and survey evidence points to behavioral biases as the main mechanism.